Decoding Strategies in Green Building Supply Chain Implementation: A System Dynamics-Augmented Tripartite Evolutionary Game Analysis Considering Consumer Green Preferences - Yanan Zhang; Danfeng Xie; Tiankai Zhen; Zhongxiang Zhou; Bing Guo; Zhipeng Dai (Buildings)
The building sector accounts for one-third of global greenhouse gas emissions, representing a significant environmental challenge in the 21st century. Green supply chain management is considered an effective approach to achieving green transformation in the construction industry. However, the green building supply chain (GBSC) involves multiple stakeholders, necessitating integrated consideration of various participants to ensure efficient GBSC implementation. In this context, and accounting for consumer green preferences, this paper identifies the government, enterprises, and consumers as key stakeholders. A tripartite evolutionary game model is established, and the influence of the participants’ strategic choices on the system equilibrium is analyzed. The model’s validity was assessed through sensitivity analysis and by comparing its outputs with findings from the existing literature. The findings show that: (1) Significant interdependence exists among GBSC participants. (2) The system will eventually tend toward an equilibrium characterized by active enterprise implementation and consumer green consumption, reducing the need for government intervention. (3) The sensitivity analysis shows that green consumption is significantly affected by the extra cost and perceived environmental benefits. These conclusions suggest that governments should build a collaborative governance system, implement dynamic and precise supervision of enterprises in stages, and optimize the incentive design for consumers to promote the implementation of the green building supply chain.